Controle preditivo baseado em modelo aplicado a um sistema com gerador de inducao duplamente alimentado para conexao com microrredes CC - Lucena, Lucas Fabrício Medeiros de (2023)
The use of renewable sources in electricity generation is the main solution found to meet the demand for electricity in a clean and sustainable way. Among these sources, wind energy stands out, growing both in Brazil and in the world, being installed on land or at sea. The generator model that has been consolidating for this energy source is the doubly fed induction generator (DFIG), with the ability to operate at variable speed and also control active and reactive power in a decoupled way. Through the growth of direct current (DC) microgrids, which can connect several generating sources to the same bus without needing to synchronize them and feed loads of different frequencies with inverters, wind system studies have been evaluated and implemented in these grids in order to take advantage of this configuration. Thus, this work uses the DFIG topology connected to the DC grid through a diode rectifier on the stator side (DFIG-DC), controlling only the rotor side converter with the finite control set model predictive control (FCS-MPC). This technique stands out both for its simplicity in using the mathematical model of the plant as the basis of its control, and also for its high dynamic performance. In this way, the behavior of the system is analyzed for two different controls: predictive current control (PCC) and predictive torque (and flux) control (PTC), performing comparisons of the main variables in steady state and transient. The system was simulated using softwares PSIM ®, Matlab ® e DevC++ ® and implemented experimentally in the laboratory for the purpose of validate the operation of the techniques in the generation system.